ENSURING THE SAFETY OF ROAD TRANSPORTATION OF GOODS - Liudmila Nikolaevna Andronikova; Nikolay Anatolievich Atrokhov; Dmitry Gennadievich Moroz (International Journal of Advanced Studies, 2017)
The article investigates Russian and foreign regulatory documents, governing the issues of cargo securing in road transport, and sets out recommendations to ensure the safety of road transportation of goods by means of their attachment.